ANALISIS ASPEK UTAMA KERANGKA KEBAHASAAN PADA SISWA SD HOMESCHOOLING USIA 7 TAHUN - Idhoofiyatul Fatin; Sofi Yunianti; Nina Veronica; Ahmad Mahmudi (STKIP Persada Khatulistiwa Sintang, 2022)
Language development milestone is generally similar in phonology, syntax, semantics and pragmatics skills. However, some children do not normally in the stage of normal milestone. It is therefore this study aims to analyze the 7 years old children language milestone. This research employed qualitative research which used case study. The subject is 7 years old girl, student in homeschooling primary school. This research investigates the girl utterance based on the conversation naturally between her teacher, mom and the girl. Then, categorizes the language development based on aspect of language framework. The result of the study illustrated that the girl have problem in phonology for spelling complicated lexical and more than three syllable. In syntax, the student cannot create simple sentence and in Semantics, the student do not understand what she reads. Moreover, the main problem is in pragmatic skill. She cannot understand the context situation and answer the questions. This indicates that the student has problem in acquiring the language